Análise do impacto de inversores inteligentes aplicados a redes de baixa tensão - Carlette, Luan Peterle (2019)
The definition by ANEEL of the rules for accessing mini and micro distributed generation, successive increases in electricity tariffs and the sharp reduction in the price of photovoltaic systems have created an ideal scenario for the expansion of distributed generation in Brazil. The micro residential photovoltaic generation is the most widespread in the country and it is connected directly to the low voltage network. Analysis of the impacts of distributed generation in this segment of the electric system is of great interest since these networks do not have equipment and resources to control voltage and are susceptible to faults caused by the high penetration levels of distributed generation. This work proposes three control strategies, applied to smart inverters, to mitigate the impacts in the voltage profile caused by this high penetration level in low voltage networks. The strategies are: constant power factor, Volt-Watt and Volt-Var control. In general, all three strategies were able to improve voltage profile. However, the constant power factor significantly increased power losses. Volt-Watt curtailed power injection, increasing investment payback time. Volt-Var was the least effective in reducing voltage levels and it also increased losses without sacrificing active power injection. Thus, choosing the best control strategy is also choosing what matters the most: low losses, high economic gains or voltage profile as close as possible to the rated voltage.